Prototype Game Education Number Box Toys sebagai Upaya Mengembangkan Keterampilan Kognitif dan Motorik Anak - Prakoso, Indro; Ayu Anggraeni Sibarani; Sarah Nurmalawati; Valent Okky Nurcahya (LPPM ITK, 2024)
Number Box Toys are children’s toys for children aged 1 to 4 years, designed to help children develop their cognitive and motor skills and learn about different number shapes and colors, including the number 0 to 9. The aim of developing this educational game prototype is to provide a visual image of the product and determine the production cost of the Number Box Toys product which is manufactured using 3D printing machine. Before making a prototype, Number Box Toys product design was created in 2D and 3D using Solidwork software, and then a Bill of Materials (BOM) and Operation Process Chart (OPC) were created. When producing the Number Box Toys prototype, simulation software was used using the Creality Slicer application to show the total time required to produce a Number Box Toys product, which was approximately 1803,78 minutes or 30,063 hours. The total time required to complete the entire operation process chart of Number Box Toys is 1822,78 minutes or about 30,38 hours, with details of 57 operation processes and 18 inspection processes. The results of calculating the production cost of the Number Box Toys educational game based on the total time required, material prices and labor costs resulted in a production cost value of Rp 404.690,89 and the selling price is Rp 465.383,03 with a profit of 15% of the cost price is Rp 60.702,13. There is a significant price difference compared to similar products sold on the market because Number Box Toys’ product prototype is made using 3D printing process, which requires a lot of time to make each part but has a size or shape that can be customized to suit the consumer.